Impact of interest rate differentials on market capitalization in Pakistan: An empirical analysis - Fatima Farooq; Sadia Anwar; Imran Sharif Chaudhry (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The current study finds out the impact of interest rate differentials on capital market. The difference between lending rate and deposit rate has been on the growing for previous few years which affects the saving behavior and investment behavior and growth of capital market. We have estimated that how interest rate factors influence the capital market of the Pakistani economy. The secondary data covering from 1975 to 2013 is collected. We have employed auto regressive distributed lags method (ARDL) for estimation. Different variables are used such as inflation, exchange rate, trade openness, money supply, indirect taxes and gross domestic product. This study finds that interest rate differentials is negatively related with market capitalization but positively related with savings and investment. However, it is also observed that factors such as inflation, exchange rate and indirect taxes are highly significant. This study concludes that interest rate difference is a key determinant of market capitalization in Pakistan. Such findings may imply that decreasing the interest rate differentials could be used as a vehicle for achieving long-term growth of capital market in Pakistan's case.
Keywords: 330; interest rate differentials; market capitalization; inflation; exchange rate; trade openness; money supply; indirect taxes; savings; investment